The Danish apprenticeship system, 1931-2002 : the role of subsidies and institutions - Albaek, Karsten [Verfasser] (My University, 2009)
"This paper provides an overview of the evolution of the apprenticeship system in a country, which provides large-scale employer-provided training for new entrants on the labour market. The overview includes institutional traits of the Danish labour market which help sustain the system by alleviating failures in the market for training. Estimation results indicate a highly significant and substantial impact of the cost variable on the inflow of apprenticies. Employment subsidies thus appear at face value to be effective in furthering training. Subsidies to employ apprentices have been an important part of the Danish educational system since 1970ies. The results of the paper might be relevant in the assessment of the relative merits and costs of similar schemes in other contries. To the extent that cross-border comparisons are relevant in the evaluation of the relative merits of educational systems, there are very few countries to look at concerning full-scale apprenticeship systems." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; G 1.3.1.1 Ausbildungsstellenmarkt; S 4.1.1 Öffentliche Finanzierung; I 2.2.1 Westeuropa; Berufsausbildung; Duales System; Beziehung Bildungssystem Beschäftigungssystem; Ausbildungsstellenmarkt; Ausbildungsvergütung; Bildungsfinanzierung; Öffentliche Ausgaben; Quantitative Angaben; 1931-2002; Dänemark